Prediction of Recurrence of Atrial Fibrillation After Radiofrequency Ablation by Frailty - Xu, Ruochen; Dong, Yan; Yadav, Nishant; Chen, Qiushi; Cao, Kejiang; Zhang, Fengxiang (Journal of the American Heart Association, 2025)
Previous studies have shown that frailty increases the risk of new-onset atrial fibrillation (AF). However, little is known about the association between frailty and the recurrence of AF after radiofrequency ablation. The objective of this study was to investigate the association between frailty and the recurrence in patients with AF who had undergone radiofrequency ablation. A total of 450 patients >50 years of age with symptomatic drug-refractory AF who had undergone catheter ablation for the first time were retrospectively enrolled. Frailty status was evaluated by the 11-factor modified frailty index and 5-factor modified frailty index. Recurrence was defined as any documented atrial tachyarrhythmia lasting >30 seconds after a 3-month blanking period without any antiarrhythmic drugs during postablation follow-up. Patients in the frail group were older, and had a higher CHA DS -VASc score, HAS-BLED score, left atrial diameter, and a higher proportion of comorbidities than those in the nonfrail group. Circumferential pulmonary vein isolation was successfully done in all of the patients. During a median follow-up of 12 months, recurrence was recorded in 98 (21.8%) patients (paroxysmal AF, 20.6%; persistent AF, 23.2%). The Kaplan-Meier analysis showed that the survival rate of freedom from atrial tachyarrhythmias in the frail group was lower than that in nonfrail groups (log-rank <0.001, 11-factor modified frailty index 31.3% versus 82.4%, 5-factor modified frailty index 44.9% versus 87.5%). After adjustment of additional risk factors in multivariable Cox analysis, 11-factor modified frailty index (hazard ratio [HR], 5.72 [95% CI, 3.79-8.64]; <0.001) or 5-factor modified frailty index (HR, 5.62 [95% CI, 3.68-8.59]; <0.001) was significantly associated with atrial tachyarrhythmia recurrence. The results remain significant in the subgroup analyses of different AF types, age groups, and sex. No significant differences of major complications were observed between the frail and nonfrail groups. In patients with AF who had undergone catheter ablation, frail patients had around a 6-fold risk of recurrence as compared with the nonfrail patients. Frailty index may be a novel risk factor of recurrent AF.